Second malignant neoplasms after treatment of non-Hodgkin's lymphoma-a retrospective multinational study of 189 children and adolescents - Attarbaschi, Andishe; Carraro, Elisa; Ronceray, Leila; Andrés, Mara; Barzilai-Birenboim, Shlomit; Bomken, Simon; Brugières, Laurence; Burkhardt, Birgit; Ceppi, Francesco; Chiang, Alan K S; Csoka, Monika; Fedorova, Alina; et al. (Leukemia, 2021)
Data on the spectrum of second malignant neoplasms (SMNs) after primary childhood non-Hodgkin's lymphoma (NHL) are scarce. One-hundred-and-eighty-nine NHL patients diagnosed in a 30 years period of 1980-2010 developing an SMN were retrieved from 19 members of the European Intergroup for Childhood NHL and/or the international Berlin-Frankfurt-Münster Study Group. Five subgroups of SMNs were identified: (1) myeloid neoplasms (n = 43; 23%), (2) lymphoid neoplasms (n = 51; 27%), (3) carcinomas (n = 48; 25%), (4) central nervous system (CNS) tumors (n = 19; 10%), and (5) "other" SMNs (n = 28; 15%). In 37 patients (20%) preexisting disorders were reported with 90% having any kind of cancer predisposition syndrome (CPS). For the 189 primary NHL patients, 5-year overall survival (OS) after diagnosis of an SMN was 56 ± 4%, being worst for patients with preexisting disorders at 28 ± 8%. Five-year OS rates were 38 ± 8%, 59 ± 7%, 79 ± 8%, 34 ± 12%, and 62 ± 11%, respectively, for patients with myeloid and lymphoid neoplasms, carcinomas, CNS tumors, and "other" SMNs (p < 0.0001). Patients with SMNs after childhood NHL having a reported CPS, mostly mismatch repair disorders, carried a very poor prognosis. Moreover, although outcome was favorable in some subtypes of SMNs after childhood NHL (carcinomas, lymphoid neoplasms), other SMNs such as myeloid neoplasms and CNS tumors had a dismal prognosis.
Keywords: kombinovaná terapie; chemoradioterapie; nehodgkinský lymfom; Humans; dítě; Child; Female; Neoplasms, Second Primary; lidé; transplantace kmenových buněk; Lymphoma, Non-Hodgkin; sekundární malignity; Follow-Up Studies; ženské pohlaví; Male; Retrospective Studies; Adolescent; prognóza; Stem Cell Transplantation; retrospektivní studie; míra přežití; Combined Modality Therapy; mužské pohlaví; Chemoradiotherapy; Prognosis; následné studie; mladiství; Survival Rate